William K. McAlister (Editor), Ordinances of the City of Nashville, to Which are Prefixed the State Laws Chartering and Relating to the City, with an Appendix, 340–41 (1881), ch. 108, § 1 - (:unkn) unknown (General Publisher, 1881)
Prohibited the carrying of pistol, Bowie knife, dirk, slungshot, brass knuckles, or other deadly weapon. Punishable by fine of $10-50 for a first offense and $50 for subsequent offenses.
--
Keywords: CARRY